1983
DOI: 10.1007/bf00927877
|View full text |Cite
|
Sign up to set email alerts
|

Light and electron microscopical studies of the location ofStrongyloides ratti in the mouse intestine

Abstract: This study was designed to define the precise anatomical location of Strongyloides ratti in the intestinal mucosa of the mouse. Light microscopy showed adult worms in vacuoles in close relationship with the columnar epithelium. Serial sections indicated that the adults wound their way circuitously through the mucosa, usually close to the crypts. Portions of worms were sometimes seen in the intestinal lumen. Electron microscopy demonstrated that adult worms were situated between the epithelial cells. They were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…7). The exposure of the worms did not seem to be the result of necrosis of epithelial cells around the worms, because enterocytes around adult Strongyloides worms usually do not show signs of necrosis (29). Based on the present results, we concluded that S. venezuelensis were active in exiting and reentering the intestinal mucosa during infection and that the inhibition of reinvasion by mast cell glycosaminoglycans caused worm expulsion.…”
Section: Adult S Venezuelensis In the Intestinal Mucosamentioning
confidence: 48%
See 1 more Smart Citation
“…7). The exposure of the worms did not seem to be the result of necrosis of epithelial cells around the worms, because enterocytes around adult Strongyloides worms usually do not show signs of necrosis (29). Based on the present results, we concluded that S. venezuelensis were active in exiting and reentering the intestinal mucosa during infection and that the inhibition of reinvasion by mast cell glycosaminoglycans caused worm expulsion.…”
Section: Adult S Venezuelensis In the Intestinal Mucosamentioning
confidence: 48%
“…Adult Strongyloides nematodes are believed to move between intestinal cells with a continuous motion of invading and exiting the epithelial layer during infection (29). If this assumption is true, adult worms would be expelled when their reinvasion is unsuccessful.…”
Section: Adult S Venezuelensis In the Intestinal Mucosamentioning
confidence: 99%
“…We have shown recently by electron microscopy that adult worms live in tunnels between the colum nar epithelial cells lining the intestinal mucosa [7], thus they are amenable to attack by various inflam matory cells. We have examined, therefore, the rela tionship between these worms and a variety of cell populations in the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…The second possibility involves the dierence in the site of parasitization of worms of different species. It has been reported that S. ratti adult worms localize between epithelial cells and above the basal membrane, whereby the epithelial cells are forced apart by adult worms (Dawkins et al 1983). On the other hand, it has been reported that T. spiralis fuses its body into the epithelial cell (Wright 1979).…”
Section: Discussionmentioning
confidence: 99%